International Perspective on Exchange Traded Funds: Their Growth and Trends in America, Asia-Pacific, Europe, Africa, and the Middle East Region - Kaur, Gurloveleen (Indian Journal of Research in Capital Markets, 2015)
Exchange-traded funds (ETFs) are open-ended managed funds, which are listed and traded on major stock exchanges around the world. They are not mutual funds in the traditional sense; rather, they are hybrid instruments combining aspects of common stocks and mutual funds and provide many of the benefits of both. An ETF seeks to generally correspond to the price and yield performance of a particular index before fees and expenses. The major aim of this paper was to ascertain and analyze the growth and trends of ETFs traded globally. The data pertained to the total number of trades, and the trading values were picked up for the period from 2003 - 2012 to check the mean, coefficient of variation, and compound growth rate of ETFs. To check the significant level of calculated CGR, the method of t - value was used. The future predictions were built to conform to the future prosperity of ETFs for the period of next 5 years, that is, from 2013 to 2017. The study suggested that appropriate regulatory and market reforms can ensure the continued success of ETFs.